The Evolution of Digital Payment Systems: The Rise of Digital Wallets and Cryptocurrencies and their Impact on Traditional Banking (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
In recent years, the landscape of financial transactions has undergone a significant transformation. The advent of digital payment systems, including digital wallets and cryptocurrencies, has revolutionized the way individuals and businesses conduct financial transactions. This article explores the rise of these technologies and their profound impact on traditional banking.